Certain Integral Transforms of Generalized $k$-Bessel Function (Analysis in Theory and Applications, 2018)
The objective of this note is to provide some (potentially useful) integraltransforms (for example, Euler, Laplace, Whittaker etc.) associated with the generalized $k$-Bessel function defined by Saiful and Nisar [3]. We have also discussed someother transforms as special cases of our main results.
Keywords: Gamma function; $k$-Bessel function; generalized $k$-Bessel function; integral transforms.